Les Songes de la nef, pour une « prise de site » musicale et sonore - Alain Bonardi (Appareil, 2018)
In this article, we develop the concept of “site taking” on a musical perspective, discussing with Jean-Louis Déotte and his writings, in the framework of our sound installation Les Songes de la nef (2018) for the the Hôtel-Dieu in Tonnerre, double tribute to the philosopher and to composer Jean-Claude Risset. Opposite to the hanging up, the “site taking” enables to think of the reception of contemporary works in heritage monuments as a dynamical relationship between both, as a “criticism” in the meaning of a remote comment between musics proposed by composer Luciano Berio. We have designed the sound installation Les Songes de la nef first of all as an instrument to build, referring to composer Helmut Lachenmann. We show that the installation is to be considered as a framework setting a certain number of relationships with the place, acoustic ones first of all. It also enables wandering visitors to discover relationships between the sound content and the Hôtel-Dieu, and therefore get a new understanding of this monument.